Validation of MIGHTI/ICON Atmospheric Wind Observations over China Region Based on Meteor Radar and Horizontal Wind Model (HWM14) - Zhou Chen; Yi Liu; Zhitao Du; Zhiqiang Fan; Haiyang Sun; Chen Zhou (Atmosphere, 2022)
The Michelson Interferometer for Global High-resolution Thermospheric Imaging (MIGHTI) on board the ICON satellite provides effective measurement of horizontal winds in the mesosphere and lower thermosphere (MLT) region. In order to verify the measurement accuracy of the horizontal wind, this study uses the measurements of the meteor radar in Wuhan and the simulation results of a horizontal wind field model (HWM14) to compare and analyze the measurement results of MIGHTI/ICON in the whole year of 2020. The comparative analysis indicated that two datasets from MIGHTI/ICON and meteor radar are strongly correlated (r = 0.65, 0.76) with an RMS difference of 39.21 m/s (30.31 m/s). The consistency for meridional wind from MIGHTI/ICON, meteor radar, and HWM14 is worse than that of zonal wind. The accuracy of horizontal wind observations is influenced by altitude, diurnal, and seasonal patterns.